Soft X‐Ray Stimulated Lanthanide@MOF Nanoprobe for Amplifying Deep Tissue Synergistic Photodynamic and Antitumor Immunotherapy. Issue 21 (29th September 2021) - Zhao, Xiaoting; Li, Youbin; Du, Linman; Deng, Zhiming; Jiang, Mingyang; Zeng, Songjun
Abstract: Combining photodynamic therapy (PDT) and immunotherapy has shown profound impact for synergistic treatment of malignant tumors. However, the shallow penetration depth of the traditional visible light activated PDT, immunosuppressive tumor microenvironment (TME), and poor immunogenicity of deep‐seated solid tumors have significantly impeded the therapeutic efficiency. Herein, a soft X‐ray activated nanoprobe is rationally engineered via integrating porphyrin Zr‐based metal–organic framework with lanthanide NaYF4 :Gd, Tb@NaYF4 scintillator nanoparticles (SNPs) by a new in situ growth strategy for synergistic PDT and immunotherapy of tumor. The nanoprobe possesses remarkably enhanced reactive oxygen species (ROS) generation triggered by soft X‐ray via further covalently grafting rose bengal on the nanoprobe, even at tissue depths of 3 cm. Moreover, the soft X‐ray induced ROS can act as potential immunogenic cell death (ICD) trigger, subsequently leading to the activation of the adaptive antitumor immune‐response. Significantly, the boosted ROS generation can further modulate the immunosuppressive TME. This work provides new strategy of designing antitumor nanoprobes for soft X‐ray triggered deep‐tissue PDT and immune response, breaking the depth barriers suffered by the traditional photoactivated PDT or ICD using visible and near infrared light. Abstract : A general in situ growth strategy of designing soft X‐ray activated lanthanide@Zr‐metal–organic framework@RB nanoprobes is developed. The designed nanoprobe presents explosive reactive oxygen species generation at deep tissue >3 cm. The findings pave the way of designing X‐ray light activated nanoprobes with integration of deep tissue photodynamic therapy, antitumor immune response activation, and modulating immunosuppressive tumor microenvironment.